Green synthesis and reflux method of CuFe2O4 and Clay/CuFe2O4 nanocomposite for photocatalysis and antioxidant studies - H. Madhu; S. Rajendra prasad (Chemistry of Inorganic Materials)
This study presents the green synthesis of CuFe2O4 and Clay/CuFe2O4 composites using neem leaf extract via a reflux method. The materials were comprehensively characterized through XRD, SEM, FTIR, EDX analysis, and UV–Vis spectroscopy. The photocatalytic efficiency was assessed for the degradation of Methyl Violet (MV) dye under UV light, achieving an outstanding 94.04 ​% degradation efficiency with the Clay/CuFe2O4 composite at an initial dye concentration of 10 ​ppm within 60 ​min. The reaction adhered to first-order kinetics, with a calculated half-life of 15.33 ​min. Furthermore, antioxidant activity evaluated using the DPPH assay exhibited a notable scavenging efficiency of 87.05 ​% and an IC50 value of 223.03 ​μg/mL for the Clay/CuFe2O4 composite, surpassing the performance of its individual components. These findings underscore the potential of Clay/CuFe2O4 composites for environmental remediation and antioxidant applications.